Foreword - Onaitis, Mark W. (Video-Assisted Thoracic Surgery, 2016)
Over the past decades, tremendous advances have occurred in minimally-invasive surgery. Video-assisted thoracoscopic surgery (VATS) has progressed from a novel procedure with widespread concern about safety and oncologic efficacy to a standard procedure that is routinely practiced by the majority of modern thoracic surgeons. The clear benefits to the patients of less pain, fewer complications, and earlier return to full activity are being realized every day across the world. As the procedure has spread quickly around the world, convincing evidence for its efficacy has lagged: randomized controlled trials of VATS and open procedures will likely never be performed due to a general lack of equipoise.